Fleksibilitas Belajar Mengajar Melalui Metode Blended Learning - Fandianta Fandianta; Guardian Yoki Sanjaya; Widyandana Widyandana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: E-learning as a new paradigm in modern education, is an alternative learning model than just face to- face. As simply, e-learning is defined as learning to use the electronic media, which aims to increase knowledge and performance. Studying by using e-learning is important to build the education sector in Indonesia, particularly as an effort to improve equity and access in education, particularly in health domain. Implementing of e-learning in health education are very relevant to the concept of continuing medical /health education that leads to continuous professional education. However, the higher education in Indonesia is still slightly to implement learning-based electronic systems. Several studies have shown the enthusiasm of higher education in using e-learning. The benefits and differences of using e-learning need to be carefully evaluated, especially for health education. This study analyzed the use of e-learning for teaching and learning in health education. In addition, identifying the barriers of e-learning for students.Method: The study was conducted in Poltekkes Kemenkes Palembang involving second-year Nursing students. A quasi-experimental approach was used for two groups of students, 1) e-learning users (treatment) and 2) non e- learning users (control), who were taking the Health Promotion subject. The data were collected using a pre-post tests and questionnaires. Data was analysed quantitatively and qualitatively.Results: Pre-post test results showed a significant difference to the increasing of students’s knowledge who is participating in e-learning compared with conventional learning (p <0,05). There is a positive perception of the discussion, assignments, quizzes / exams, and the availability of teaching materials amongst the students who are participating in e-learning.Conclusion: Blended learning method provide a positive impact on teaching and learning in nursing students. This method should be considered as a complement to conventional learning.